Connecting South Asia to Southeast Asia: Cross-border infrastructure investments - Jean-Francois Gautrin (Asian Development Bank Institute (ADBI), 2014)
South Asia and Southeast Asia have been connected for many centuries, with the degree of connectivity varying over time. This paper explores strengthening connectivity between the two subregions by identifying the missing links in transport connectivity. The paper is specifically concerned with the role of cross-border transport infrastructure investments. To this end, the author reviews all possible road and rail land corridors that would help create seamless transport connectivity. Missing gaps and corresponding transport infrastructure projects are identified, and projects are screened and prioritized. For the selected critical projects, the study recommends phased investments.
Keywords: H41; H54; O22; F36; 330; cross border infrastructure investments; South Asia and Southeast Asia; seamless infrastructure; road and rail land corridor